Analisi Terhadap Penyehatan Perusahaan Melalui PKPU yang Berkeadilan - Tami Rusli (KEADILAN PROGRESIF, 2016)
Settlement of debts which could lead to bankruptcy debtor, in order to avoid gaps in implementation, bankruptcy was supposed to be an institution that is final, that is to say before the bankruptcy of the debtor "should" be given the opportunity to perform Suspension of Payment ( "PKPU") in advance. the research problem is how to restructure the company through PKPU? The method used in this research using normative juridical approach. The results showed that the way of restructuring the company melauli PKPU is where the aspects of feasibility and good faith plays an important role and more decisive than the state technically solvent or insolvency of a company. For the debtor applicant must PKPU transparent and equitable and promoting honesty, decency by lifting an independent consultant to draw up a peace plan.